Peran Penyuluh dalam Meningkatkan Adopsi Inovasi Petani pada Program Kartu Petani Berjaya di Kecamatan Gadingrejo : The Role of Extention Workers in Increasing Adoption Innovation of Farmers in the Program Kartu Petani Berjaya in Gadingrejo Sub-district - Reinata Rhamadanti Putri; Indah Listiana; Dewangga Nikmatullah; Muhammad Ibnu (Journal of Agriculture and Social Development, 2023)
The distribution of subsidized fertilizers is one of the problems experienced by farmers, in thisregard the Province of Lampung initiated the Program Kartu Petani Berjaya(KPB). Program KPB is an innovation to minimize errors in the distribution of subsidized fertilizers. In implementing the Program KPB , an extension agent can play a role in the adoption of Program KPB Program innovations by farmers. This study aims to determine the role of extension workers in increasing the adoption of farmer innovations in the implementation of the Program Kartu Petani Berjaya (KPB). This research was conducted in Gadingrejo District, Pringsewu Regency. Respondents were 46 farmers from representative farmer groups in 6 different villages with the highest rice production yields based on the target area of each extension workers. The results showed that the role of extension workers in this study was in the medium category, the level of adoption of farmer innovations in the implementation of the Program KPB was in the medium category, and from the research it was known that the role of extension agents had an effect on increasing the adoption of farmer innovations in the implementation of the Program KPB in Gadingrejo District.